Cardiopulmonary resuscitation knowledge toward motivation of anesthesiology students in providing emergency assistance - Fitnaningsih Endang Cahyawati; Maulidah Maulidah; Nur Rah Mulyo (Universitas 'Aisyiyah Yogyakarta, 2022)
Emergency conditions can occur in areas far from the presence of health workers. The role of the community or event students to help victims in emergencies becomes very important before being handled by health workers. This study aimed to determine the relationship between knowledge about cardiopulmonary resuscitation and the motivation of anesthesiology students to provide emergency assistance. This research was cross-sectional research at Aisyiyah University, Yogyakarta. The sample in this study was students of anesthesiology of 54 students. There was a relationship between knowledge of cardiopulmonary resuscitation and anesthesiology students' motivation to provide emergency assistance.